We Need a Past to Create the Present: The Significance of Tradition in the development of Theatre for Young People in Malaysia - Janet Pillai, (Wacana Seni Journal of Arts Discourse, 2002)
Many seminal directors of young people's theatre in Malaysia have drawn upon the theatrical models of the West as well as consciously or unconsciously 'borrowed' from their own traditional cultures. The borrowings from traditional theatre often began with the recovery of traditional content, the unearthing of form, and finally the marrying of the two. These fragments of borrowings were subject to constant redefinition, that is, they were placed alongside modern ideas, juxtaposed against the western, synthesized, or reinvented to create new theatre.